(untitled) (Journal of the Spanish Institute for Strategic Studies, 2013)
Since 2009, the United States is carrying out a campaign of air strikesagainst al Qaeda in the Arabian Peninsula, with an increasing use of unmannedcombat aerial vehicles. This paper analyzes the causes that explainthe origin of the campaign describes its main characteristics and values itsconsequences.